Dynamism : The Values That Drive Innovation, Job Satisfaction, and Economic Growth - Phelps, Edmund S.; Bojilov, Raicho; Hoon, Hian Teck (Cambridge, MA : Harvard University Press, 2020)
Nobel Laureate Edmund Phelps argues that the high level of innovation in the West was not a result of scientific discoveries plus entrepreneurship. Rather, modern values—particularly the individualism and self-expression prevailing among the people—fueled the dynamism needed for widespread innovation.
Frontmatter -- Contents -- Preface -- Introduction: A Theory of Innovation, Flourishing, and Growth -- Overview of the Chapters -- 1. Innovation: The Source of Rapid Growth -- 2. Sources of Indigenous Innovation and Channels of Its Transmission across Countries -- 3. Indigenous Innovation during the IT Revolution: We Never Had It So Good? -- II. THE ROOTS AND BENEFITS OF INNOVATION -- 4. A Case Study of Iceland’s Successful Innovators -- 5. The Force of Values -- 6. Individual Values, Entrepreneurship, and Innovation -- 7. Innovation, Job Satisfaction, and Performance in Western European Countries -- 8. Growth Effects of Additive and Multiplicative Robots alongside Conventional Machines -- 9. Wage Effects of Additive and Multiplicative Robots alongside Factory Buildings and Physical Structures -- 10. Additive Robots, Relative Prices, and Indigenous Innovation -- Epilogue -- Notes -- Acknowledgments -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Apr 2020)
Keywords: Economic development; Entrepreneurship; Individualism; Job satisfaction; Technological innovations; BUSINESS & ECONOMICS / Free Enterprise